Perencanaan Strategi Sistem Dan Teknologi Informasi Pada PT. Microsis - Widjaja, Henry Antonius Eka (Bina Nusantara University, 2010)
The purpose of this study is to analyze the company's business processes and make strategic planning and information technology system that is suitable for supporting the goals and vision of the company's mission. The research method is data collection in the form of interviews with the company management and staff, field observations, literature research related to strategic planning and information technology systems. The results of this study prove that the company has a weakness in the implementation of information systems which is not maximized , while the strength of the company has not been fully supported by the use of information technology . This shows that the need for strategic planning and information technology systems to support achievement of business strategy at the company over the next five years. Thus, this research produced a strategic plan in the form of application architecture, hardware architecture, network architecture, organizational development, implementation schedule and cost estimates.